Genetic counselling - Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
Genetic counselling is a relatively new medical activity. There.are some conditions that usually need genetic counselling.•The classification of genetic disorders, their mode of inheritance and the method of establishing the diagnosis must be well understood before giving the counselling. The mode of inheritance of genic disorders and some difficulties in the diagnosis need special attention. Chromosomic disorders and embryopathies have been shortly explained ,as well.Finally, a short explanation of prenatal diagnosis, carrier detection and some methods of treating genetics disorders have been proposed so that genetic counselling can be given effectively.Key Words: genetic counselling - genetic disorders - genic disorders - prenatal diagnosis - carrier detection.